Utilizing surface plasmon resonance as a novel method for monitoring in-vitro P-glycoprotein efflux - Nguyen, Phuong H.; Cui, Shuolin; Kozarich, Amanda M.; Rautio, Alex; Roberts, Arthur G.; Xiong, May P. (Frontiers in Biophysics, 2024)
P-glycoprotein (Pgp) is known for its dichotomous roles as both a safeguarding efflux transporter against xenobiotics and as a catalyst for multidrug resistance. Given the susceptibility of numerous therapeutic compounds to Pgp-mediated resistance, compliance with Food and Drug Administration (FDA) guidelines mandates an in-depth in vitro transport assay during drug development. This study introduces an innovative transport assay that aligns with these regulatory imperatives but also addresses limitations in the currently established techniques. Using Pgp-reconstituted liposomes and employing surface plasmon resonance (SPR), this study developed a distinct method of measuring the relative transport rates of Pgp substrates in a controlled microenvironment. The Pgp substrates selected for this study – quinidine, methadone, and desipramine – resulted in transport ratios that corroborate with trends previously observed. To assess the kinetics of Pgp-mediated transport, the results were analyzed by fitting the data to both currently proposed Pgp substrate translocation models – the vacuum cleaner and flippase models. While the resulting kinetic analysis in this study lends support predominantly to the vacuum cleaner model, this study most notably developed a novel method of assessing Pgp-mediated transport rates and real-time kinetics using SPR.